Comparing Free Play and Partly Structured Play in 4-5-Years-Old Children in an Outdoor Playground - Tortella, Patrizia; Haga, Monika; Ingebrigtsen, Jan Erik; Fumagalli, Guido Francesco; Sigmundsson, Hermundur (Frontiers in Public Health, 2019)
The aim of this study was to compare how the organization of a movement session as partly structured play or free play influenced the physical activity engagement in 4-5 years old pre-schoolers. The partly structured playgroup consisted of 46 children and the free playgroup consisted of 33 children. The playground activities consisted of 10 sessions each lasting 1 hour, executed once per week in the period Mars to May 2017 at a specific playground setting. The partly structured playgroup conducted a movement activity session that included a combination of both structured- and free play activities. The free playgroup engaged in unstructured play, only. To detect the intensity of the physical activity each child carried an accelerometer 1 hour the first week and last week of the intervention. Results indicate a significant difference in physical activity level between the two groups for the 5-year-old in the favour of the partly structured playgroup. There was a significant difference between the four-and 5-year-old in relation to physical activity level. No significant difference between the activity in March and May for the whole group was found.